Parameter variations within Li-Ion battery packs – Theoretical investigations and experimental quantification. (August 2018) - Baumann, Michael; Wildfeuer, Leo; Rohr, Stephan; Lienkamp, Markus
Highlights: Theoretical and experimental investigation of parameter spreads and their mutual influences with load imbalances. Experimental quantification of parameter variations in new and aged cell batches. Strength of correlation analysis between capacity and resistance increases during aging. Increased cell-to-cell and couple-to-couple capacity spread during aging. Abstract: Single lithium-ion cells within electric vehicles' battery packs generally show variations in capacity and impedance due to the manufacturing process as well as operational conditions. Therefore, cells connected in parallel experience different dynamic loads during vehicle operation, which may potentially result in uneven and accelerated aging behavior. However, in literature only little is mentioned about the different reasons for parameter variations within single cells of parallel connections as well as their magnitude in real-life conditions. In this work, capacity and impedance variations within parallel-connected cells are investigated theoretically and are quantified exemplary by a batch of new cylindrical 18650 cells as well as an retired BEV battery pack with a 2p96s configuration of prismatic cells. Furthermore, the development of existing parameter variations along cycling are analyzed for two modules of the battery pack. It is demonstrated, that the aged cells show a strong increased parameter spread compared to the new cells. During further aging, the existing capacities spread of the block and especially the state of inhomogeneity of parallel couples increases. Hence, the widespread theory of a self-balancing effect inside a parallel connection, which leads to a convergence of the cells' SOH, is disproved.